The concept of creating an automated information and computing complex for substantiating projects of programs and plans for the development of arms and means of radiation, chemical and biological protection - D. N. Cheshev; A. S. Durnov; S. V. Skoblikov; D. A. Egorushkin (Вестник войск РХБ защиты, 2020)
The new stage of military construction makes it necessary to apply more advanced approaches to the functioning of the program management system for the development of weapons in order to adequately respond to emerging problems related to the formation, implementation and adjustment of plans to strengthen the country's defense in accordance with the current military – political and economic conditions of their implementation. The trend towards a continuous increase in the volume of processed information, strengthening of requirements to the efficiency of the formation of projects, programmes and plans of military construction, as well as the accuracy of the models and methodologies used to predict outcomes of activities in the field of defence and security of the country, determine the relevance of a comprehensive automation of the processes of substantiation of prospects of development of arms and means of radiation, chemical and biological protection, which can be provided by the introduction of modem information technologies, advanced methods of data analysis and improved scientific and methodological support into the practice of software management of weapons development. The purpose of the research is to create an information and computing complex to support decision-making on improving the armament system of radiation, chemical and biological protection on the basis of modern information computer technologies and methodological support for the justification of programs and development plans of arms and means of radiation, chemical and biological protection. The work is based on the methods of database design and development, system analysis, relational algebra, and object- oriented approach to the formation of automated systems. In the course of the research conceptual provisions were developed, that define the circuit operation, the structure and content of the database information and computing complex, organization of the automated information and analytical work in support of decision-making in development of arms and means of radiation; chemical and biological protection.